Recognition the Synoptic Conditions of Extreme and Widespread Precipitations in Caspian Western Coasts by Emphasis on Atmosphere Thickness Patterns - AmirHossein Halabian; Freshta Hosseinali Pourjazi (جغرافیا و پایداری محیط)
To do the synoptic analysis of extreme and widespread precipitations in Caspian western coasts, daily precipitation data from 1340/1/1 to 1 on the 14×1383/11/10 (15992 days) interpolated by Kriging method. These data provide to calculate maximum precipitation and area percent under precipitation for each day including precipitation. On this basis, were identified the most extreme and the most widespread regional precipitations and were selected severe precipitation by 99th percentile base index. Using environment- circulation approach and agglomerative hierarchical cluster analysis by “Ward” method, we could identify three circulation patterns of atmosphere thickness between 500-1000 hpa levels which were effective for creating the extreme and widespread precipitations of Caspian western coasts. However these patterns have many similarities, but, they are considered as different patterns for these regions. Then, to analyze the precipitations in every atmosphere thickness pattern, the representative day was defined on the basis of correlation coefficient with 95% threshold and in these days, sea level pressure maps, atmosphere thickness in 500-1000 hpa levels, functions of frontgenesis and humidity convergence flux were mapped and analyzed for 500, 600, 700, 850, 925 and 1000 hpa levels. The results show that the relatively deep trough on the north and northwest sections of Caspian Sea between Caspian Sea and Black sea can make background for occurring the extreme and widespread precipitations in studied region. The analysis of frontgenesis function maps in the Caspian western coasts confirms the existence of front core on the Caspian Sea and around it too. The analysis of humidity convergence flux indicate that Caspian sea is the most important source of providing the humidity of western coasts precipitations of this sea, and Black sea and Aral lake are in the next importance rankings.